PTU-023 Long-term outcomes following drug-eluting bead transarterial chemoembolisation (DEB-TACE) as part of multimodality treatment for hepatocellular carcinoma. (28th May 2012) - Lever, C; Kumar, P; George, S; Hacking, N; Stedman, B; Breen, D; Pearce, N; Wright, M
Abstract : Introduction: Treatment protocols for hepatocellular carcinoma (HCC) are evolving rapidly. We sought to determine long-term outcomes in patients with HCC treated with DEB-TACE as stand alone or part of multimodality treatment at a single centre. Methods: Our departmental database of HCC, diagnosed using EASL radiological criteria, was reviewed retrospectively. From August 2006 to January 2011, 80 patients (60 males/20 females) underwent DEB-TACE some of which also had surgery and/or percutaneous ablation. A total of 186 episodes of DEB-TACE treatment were performed (minimum 1 episode and maximum 8 episodes per patient). 37.5% of patients presented with multifocal disease, a further 7.5% presented with tumour plus satellites. The mean MELD (model for end-stage liver disease) in this cohort was 9.53 (range 6–22). Demographics, procedural details, clinical measures and outcomes were studied. Median age was 69 years (range 33–87). All patients were included in the survival analysis. Overall survival was described using Kaplan–Meier methods. Results: 53 patients with a median tumour size of 49 mm (range 12–163 mm) were treated with DEB-TACE alone with a mean number of procedures of 2.1. Here median survival was 28.5 months (798 days). The 1- and 3-year survival rates in this group where 66% and 38% respectively. 27 patients (median tumour size of 40 mm (range 12–100 mm)) were treated with a combination of therapies and at 55 months (1540 days) the median survival had not been reached. Survival in this group was 51.1% at time data collection. In this group the 1- and 3-year survival rates were 86% and 64% respectively. In our cohort of patients DEB-TACE both with or without combination therapies, resulted in median survival of 44 months. Overall survival rates at 1- and 3-years were 74.5% and 50.3% respectively. There were no deaths at 30 days following a DEB-TACE episode. Conclusion: In our centre this procedure is safe and well tolerated with multimodality treatment showing an improved survival outcome. Our results highlight the importance of a multidisciplinary approach with the application of multimodal therapy in the management of HCC with an improved survival for appropriately selected patients. Competing interests: None declared.